Neural correlates of script-driven imagery in adolescents with interpersonal traumatic experiences: A pilot study. (30th September 2020) - Malejko, K.; Tumani, V.; Rau, V.; Neumann, F.; Plener, P.L.; Fegert, J.M.; Abler, B.; Straub, J.
Highlights: Listen to trauma scripts revealed activity in the thalamus, dACC, dmPFC, amygdala. Amygdala-activity correlated positively with depression symptom-severity. We demonstrate the feasibility of fMRI during a trauma imagery task in adolescents. The task could be useful to investigate neural mechanisms of treatment effects. Abstract: In adults, trauma imagery has proven to be a useful tool to assess the neural mechanisms of psychological trauma processing. In adolescents, heterogeneous results could be found for other tasks, however, a trauma imagery paradigm has not been evaluated. For this purpose, we investigated a trauma imagery paradigm with control scripts to assess neural correlates of traumatic experiences in youth. 15 adolescents, who had experienced a traumatic interpersonal event in the past and have developed clinically relevant symptoms, underwent an fMRI scan while listening to their individual trauma- versus two control scripts (positive/negative). We analysed a parametric contrast of the imagery phases (trauma > negative > positive) which revealed activity in the thalamus, dorsal anterior cingulate cortex, cuneus, dorsomedial prefrontal cortex and amygdala. Additionally, amygdala-activity correlated positively with depression-symptom-severity. Our data provide evidence for the feasibility of fMRI during a trauma imagery task in adolescents to investigate networks previously related to hyperarousal in adults with PTSD. Further, we demonstrate the specificity of the activated networks for trauma imagery as compared to imagery of other emotional situations. The task might be particularly useful to evaluate neural correlates of treatment in adolescents when hyperarousal is a target symptom.